A gender analysis of the English language textbook "English for Iraq" used in the fifth preparatory classes in the Iraqi preparatory schools: an evaluative study - Al-Asadi, Mahdi Mohsin Mohammed (جامعة البصرة - كلية التربية للعلوم الإنسانية, 2014)
على الرغم من أن العديد من المجتمعات، في جميع أنحاء العالم، والعراق من بينها، قد بدأت في تبني مواقف جديدة تجاه المرأة وأدوارها في بناء المجتمعات، إلا أننا لا نزال نستطيع العثور على نفس وجهات النظر القديمة المتحيزة ضد المرأة في معظم الكتب المدرسية المعدة لمتعلمي اللغة الإنجليزية من غير متكلميها. إن هذه الدراسة هي محاولة لاستكشاف حالة التمييز على أساس الجنس في الكتاب المدرسي الحالي "الإنجليزية للعراق" المستخدم في الصفوف الخامسة في المدارس الإعدادية العراقية. وقد كشفت هذه الدراسة عن جوانب كثيرة من التمييز على أساس الجنس في هذا الكتاب المدرسي. وهذا يدل على أن المرأة في كتاب اللغة الإنجليزية "اللغة الإنجليزية للعراق" هي أقل وضوحاً من الرجال كشخصيات، وقد تم تصويرها في الأدوار النمطية من المهن lthough many societies, all over the world and Iraq amongst them, had started to adopt new attitudes towards women and their roles in building the societies, we still can find the same old sexist views exist in the majority of the EFL textbooks. This study is an attempt to explore the status of sexism in the current EFL| textbook "English for Iraq" used in the fifth preparatory classes in the Iraqi preparatory schools. The study uncovers many aspects of sexism in this textbook. It shows that the women in the English language textbook "English for Iraq" are less visible than men as characters, and are portrayed in stereotypical roles with occupations.
نص الرسالة باللغة الإنجليزية
Keywords: تحليل المحتوى -- المرأة -- التعليم المتوسط -- العراق -- الكتب المدرسية -- تدريس اللغة الإنجليزية